Identifikasi Kesalahan Siswa Kelas VII Dalam Menyelesaikan Soal Cerita Geometri Dengan Newman’s Procedure - Hadiyanto, Fahrur Rozi; Wulandari, Nourma Pramestie (Mandalika Mathematics and Educations Journal, 2019)
Errors in solving geometry problems can be used as a reference to find out what difficulties are made by students. One of the efforts in helping students who have difficulty in solving geometry problems, is by identifying the results of students' completion of the given problem. The purpose of this study is to identify student errors in solving geometry problems using NewmanÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s Procedure. This study uses a mixed approach (fixed method) using test questions instruments. The subjects of this study were 29 students of class VII C of SMP Negeri 8 Kediri. The results of identification of student answers obtained data that errors in reading problems because students are confused about solving the geometry problems. Comprehension errors of what they read happens because students answer broadly when asked is that many tiles are needed. Transformation errors occur because students incorrectly write numbers while working. Errors in process skill in implementing strategies occur because students choose the wrong strategiy in solving problems. Errors in encoding when students write final answers occur because students do not know that writing down the distance unit while working on problems is not allowed and itÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s wrong in counting.AbstrakKesalahan dalam menyelesaikan soal geometri dapat dijadikan acuan untuk mengetahui kesulitan-kesulitan apa saja yang dilakukan oleh siswa. Salah satu upaya dalam membantu siswa yang kesulitan dalam menyelesaikan soal geometri, yaitu dengan mengidentifikasi hasil penyelesaian siswa terhadap soal yang diberikan. Tujuan dari penelitian ini adalah untuk mengidentifikasi kesalahan siswa dalam menyelesaikan soal geometri dengan menggunakanÃƒÂ‚Ã‚Â NewmanÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s Procedure. Penelitian ini menggunakan pendekatan campuran (fixed method)ÃƒÂ‚Ã‚Â dengan menggunakan instrument soal tes. Subjek penelitian ini ada 29 siswa kelas VII C SMP Negeri 8 Kediri. Hasil identifikasi jawaban siswa diperoleh data bahwa kesalahan dalam membaca soal dikarenakan siswa bingung menyelesaikan soal geometri tersebut. Kesalahan dalam memahami apa yang dibaca terjadi dikarenakan siswa menjawab luas pada saat yang ditanyakan adalah banyak ubin yang dibutuhkan. Kesalahan transformasi terjadi dikarenakan siswa salah menulis angka saat mengerjakan. Kesalahan dalam menerapakan strategi terjadi karena siswa salah memilih strategi dalam menyelesaikan soal. Kesalahan menuliskan jawaban akhir terjadi karena siswa tidak tahu bahwa menuliskan satuan jarak saat mengerjakan soal tidak diperbolehkan dan salah dalam menghitungÃƒÂ‚Ã‚Â ÃƒÂ‚Ã‚Â